A Self-Setting Hydrogel of Silylated Chitosan and Cellulose for the Repair of Osteochondral Defects: From in vitro Characterization to Preclinical Evaluation in Dogs - Boyer, Cécile; Réthoré, Gildas; Weiss, Pierre; d’Arros, Cyril; Lesoeur, Julie; Vinatier, Claire; Halgand, Boris; Geffroy, Olivier; Fusellier, Marion; Vaillant, Gildas; Roy, Patrice; Gauthier, Olivier; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Articular cartilage (AC) may be affected by many injuries including traumatic lesions that predispose to osteoarthritis. Currently there is no efficient cure for cartilage lesions. In that respect, new strategies for regenerating AC are contemplated with interest. In this context, we aim at developing an injectable, self-hardening, mechanically reinforced hydrogel (Si-HPCH) composed of silanised hydroxypropymethyl cellulose (Si-HPMC) mixed with silanised chitosan. The in vitro cytocompatibility of Si- HPCH was tested using human adipose stromal cells (hASC). In vivo, we first mixed Si-HPCH with hASC to observe cell viability after implantation in nude mice subcutis. Si-HPCH associated or not with canine ASC (cASC), was then tested for the repair of osteochondral defects in canine femoral condyles. Our data demonstrated that Si-HPCH supports hASC viability in culture. Moreover, Si-HPCH allows the transplantation of hASC in the subcutis of nude mice while maintaining their viability and secretory activity. In the canine osteochondral defect model, while the empty defects were only partially filled with a fibrous tissue, defects filled with Si-HPCH with or without cASC, revealed a significant osteochondral regeneration. To conclude, Si-HPCH is an injectable, self-setting and cytocompatible hydrogel able to support the in vitro and in vivo viability and activity of hASC as well as the regeneration of osteochondral defects in dogs when implanted alone or with ASC.